Reading Disfluencies and Strategy To Overcome it: A Study Case in First Semester Students of English Department UHKBPNP - Siska Anggita Situmeang; Novra Melisa P. Hutabarat; Triputri Harefa (Jurnal Ilmu Sosial dan Humaniora, 2026)
This proposal is about a research on the categorization of the reading disfluency produced by the university students in Indonesia. The research is conducted in the teacher training, FKIP Universitas HKBP Nommensen Pematangsiantar. The study is conducted on the classroom conversation of the First semester students studying Reading Comprehension subject in the academic year 2024/2025. The research will explore how the students produce each type of the category existed in every clause they produce in their reading. the findings of this study can be very important information to understand the students’ disfluency in the reading classroom